Tanult orvosok a középkori Magyar Királyságban - Haraszti Szabó, Péter; Kelényi, Borbála (Gerundium, 2016)
learned Medical doctors of the Medieval hungarian KingdoM. he present paper aims at collecting the particulars of medical doctors of the medieval Hungarian kingdom, primarily the ones belonging to persons who attended a university. he research had to reckon with the fact that the doctors were referred to in the respective sources by several Latin names (doctor in medicine, medicus, physicus, barbitonsor, etc.) but not all of these refer to a person who attended a university. We accept only the person as a learned doctor whose university attendance can be documented either by his presence in the matricula of a university or by his degree mentioned in a source. Another attendant problem was the deinition of Hungarian, since, for example, most doctors practising in the royal court came from abroad but owing to their service they often gained Hungarian citizenship or, moreover, nobility. After examinig these questions we managed to collect 69 persons who have evidence of their studies or graduation from 1226 till 1525, mainly from the second part of the 15th century or the irst quarter of the 16th century. heir prosopographical data can be found in the Database at the end of the paper. Most of the students studied medicine in Vienna (22 persons) or at an Italian university (31 persons) and almost half of them gained a degree (35 persons). In accordance with the present phase of the research most doctors had an ecclesiastical career, mainly as a canon (12 persons), however, a few of them practised as municipal physicians (15 persons).